2021
DOI: 10.1097/tp.0000000000003754
|View full text |Cite
|
Sign up to set email alerts
|

Complement Blockade in Recipients Prevents Delayed Graft Function and Delays Antibody-mediated Rejection in a Nonhuman Primate Model of Kidney Transplantation

Abstract: Original Basic ScienceBackground. Complement activation in kidney transplantation is implicated in the pathogenesis of delayed graft function (DGF). This study evaluated the therapeutic efficacy of high-dose recombinant human C1 esterase inhibitor (rhC1INH) to prevent DGF in a nonhuman primate model of kidney transplantation after brain death and prolonged cold ischemia. Methods. Brain death donors underwent 20 h of conventional management. Procured kidneys were stored on ice for 44-48 h, then transplanted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 90 publications
(182 reference statements)
1
12
0
Order By: Relevance
“…In animal models, complement depletion or inhibition attenuates myoglobin 34 , proteinuria 29 and ischemia/reperfusion [35][36][37][38] -induced tubular damage and interstitial fibrosis. However, clinical data are particularly scarce and limited to trials assessing C5 blockade in renal transplantation associatedischemia reperfusion and that has yielded disappointing results 39 .…”
Section: Complement Activation In Kidney Diseases Beyond the Glomerulusmentioning
confidence: 99%
“…In animal models, complement depletion or inhibition attenuates myoglobin 34 , proteinuria 29 and ischemia/reperfusion [35][36][37][38] -induced tubular damage and interstitial fibrosis. However, clinical data are particularly scarce and limited to trials assessing C5 blockade in renal transplantation associatedischemia reperfusion and that has yielded disappointing results 39 .…”
Section: Complement Activation In Kidney Diseases Beyond the Glomerulusmentioning
confidence: 99%
“…Although these three pathways are engaged by distinct molecular mechanisms, all of them lead to the cleavage of the C3 protein, generating the C3a and C3b fragments ( 118 ). Two recent studies have demonstrated that in a nonhuman primate model, C3 complement inhibition can prevent antibody-mediated injury and improve transplant outcomes ( 119 , 120 ). Ultimately, full complement cascade activation leads to the cleavage of C5, generating the soluble C5a and C5b fragments.…”
Section: Mechanisms Involved In Antibody-mediated MVImentioning
confidence: 99%
“…Thus far, the clinical need for plasma purified or recombinant (which has become available) C1‐INH is not in a complement disease but rather in hereditary or acquired angioedema, which is characterized by uncontrolled generation of bradykinin. However, clinical trials have been or are underway to investigate if C1‐INH may be efficacious in complement diseases with a substantial CP component, such as antibody‐mediated rejection after kidney transplantation or overshooting inflammation after severe traumatic brain injury 79,80 . Future studies will show whether C1‐INH, which inhibits more than one physiological pathway, warrants in depth investigation as a complement inhibitor in diseases with a substantial CP involvement now that a specific monoclonal antibody directed against C1s has been approved for clinical use.…”
Section: “Prominent” Complement‐mediated Diseases Pathophysiology And...mentioning
confidence: 99%